2016
DOI: 10.1002/jcph.736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Proposed In Vivo Probe Substrates and Inhibitors for Phenotyping Transporter Activity in Humans

Abstract: Drug transporters are present in various tissues and have a significant role in drug absorption, distribution, and elimination. The International Transporter Consortium has identified 7 transporters of increasing importance from evidence of clinically significant transporter-mediated drug-drug interactions. The transporters are P-glycoprotein, breast cancer resistance protein, organic anion transporting polypeptide (OATP) 1B1, OATP1B3, organic cation transporter 2, organic anion transporters (OAT) 1, and OAT3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 152 publications
(398 reference statements)
1
18
0
Order By: Relevance
“…Pitavastatin, rosuvastatin, and atorvastatin are widely used as clinical probe drugs for the evaluation of organic anion transporting polypeptide 1B1/1B3 (OATP1B)‐mediated DDIs, either following a clinically relevant oral dose or a microdose as part of a drug cocktail ( Figure and Table ). Although considered as OATP1B substrates, the aforementioned drugs as well as other proposed “probes” have been shown to be substrates for other transporters in vitro , such as OATP2B1, sodium‐taurocholate co‐transporting polypeptide (NTCP), breast cancer resistance protein (BCRP), P‐gp, organic anion transporter 3 (OAT3), and multidrug resistance‐associated protein 4 (MRP4) and MRP3 …”
Section: State‐of‐the‐art In Clinical Probe Drugs and Potential Endogmentioning
confidence: 99%
“…Pitavastatin, rosuvastatin, and atorvastatin are widely used as clinical probe drugs for the evaluation of organic anion transporting polypeptide 1B1/1B3 (OATP1B)‐mediated DDIs, either following a clinically relevant oral dose or a microdose as part of a drug cocktail ( Figure and Table ). Although considered as OATP1B substrates, the aforementioned drugs as well as other proposed “probes” have been shown to be substrates for other transporters in vitro , such as OATP2B1, sodium‐taurocholate co‐transporting polypeptide (NTCP), breast cancer resistance protein (BCRP), P‐gp, organic anion transporter 3 (OAT3), and multidrug resistance‐associated protein 4 (MRP4) and MRP3 …”
Section: State‐of‐the‐art In Clinical Probe Drugs and Potential Endogmentioning
confidence: 99%
“…In addition, recent in vitro studies have shown no significant transporter inhibition for therapeutic phosphorothioate ASOs (Yu et al, 2016;Shemesh et al, 2017). Furthermore, a clinical interaction study with metformin, a drug transported by OCT1, OCT2, and multidrug and toxin extrusion MATE1/MATE2 (Momper et al, 2016), and a therapeutic phosphorothioate ASO (ISIS-113715) reported no clinical DDI (Geary et al, 2006). Given the lack of transporter interactions in literature reports, the inhibition of transporters by the generic oligonucleotides used in this study is through an unknown mechanism and the implications are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo f t can be estimated using pharmacogenetic data in humans through mathematical modeling (Li, ). Clinical sensitive probe substrates and inhibitors for the major transporters have been reviewed (Chu et al, ; Momper, Tsunoda, & Ma, ).…”
Section: Transporter‐mediated Ddimentioning
confidence: 99%